Coordination Behaviour of Some New Schiff Bases Towards Co(II), Ni(II) and Cu(II) - BALA , MANJU; I. P. SINHA, A. (Asian Journal of Chemistry, 2010)
Some new Schiff bases are synthesised from 2-pyridinecarboxaldehyde with 2-aminobenzimidazole(L1), 3-amino-1,2,4-triazole(L2) and 2-amino- 3-hydroxypyridine(L3). Cobalt(II) chloride and nickel(II) chloride complexes of Schiff bases have the stoichiometry [M(L)(H2O)] Cl2(M ═ Co(II) and Ni(II), L ═ Schiff base) while copper(II) chloride complexes have the stoichiometry [Cu(L)2]Cl2.H2O. The complex compounds have been isolated and characterized by elemental analyses, electrical conductivity, magnetic measurements, and infrared spectral measurements. All Schiff bases act as tridentate ligand towards Co(II) and Ni(II), but in case of Cu(II) complexes, they behave as bidentate ligand.